Biodistribution of a Nonpeptidic Fluorescent Endothelin a Receptor Imaging Probe - Carsten Höltke; Jens Waldeck; Klaus Kopka; Walter Heindel; Otmar Schober; Michael Schäfers; Christoph Bremer (Molecular Imaging)
Biodistribution studies are essential for understanding the biologic behavior of novel fluorochrome-based molecular imaging agents. In this study, the biodistribution of a recently developed fluorescent imaging probe with high affinity to the endothelin A (ET A ) receptor was evaluated by fluorescence reflectance imaging (FRI). CD-1 mice were injected with 2 nmol of the probe intravenously and sacrificed at various time points. Tissue samples of the heart, spleen, lung, kidneys, liver, brain, and muscle were removed and imaged by FRI. Initially, the signal intensity (SI) was highest in lung, kidney, and liver tissue, followed by the heart, whereas spleen, muscle, and brain showed the lowest SI. In the kidneys, the SI decreased rapidly. In the heart, an initial SI increase was observed, followed by SI attenuation, whereas in the lung, the SI steadily increased. Competition experiments showed a significant ( p #x003C; .005) degree of specific binding in the heart, with a reduction in SI of > 50%. In conclusion, FRI allows us to perform biodistribution studies of novel fluorescent tracers. The developed imaging probe can be exploited to image ET A receptor expression ideally 30 minutes to 3 hours after injection.